Analisis Pertimbangan Hukum Terkait Pelanggaran Hak Cipta “Urban Light” (Studi Putusan No 31/Pdt.Sus-Hak Cipta/2020/Pn.Niaga.Jkt.Pst) - Raudah, Bunga; Saidin; Sitepu, Faradila Yulistari (Acta Law Journal, 2025)
This study aims to analyze the legal considerations related to copyright infringement in the case of "Urban Light," as presented in decision number 31/Pdt.Sus-Hak Cipta/2020/PN.Niaga.Jkt.Pst. This case involves a lawsuit filed by Nancy J. Rubins, the heir of the creator of the artwork "Urban Light," Chris Burden, against Defendant I, PT Pasti Makan Enak, and Defendant II, Henry Husada, who are accused of copying and modifying the artwork into the installation "Love Light" without permission.In this research, the author examines the legal framework of copyright in Indonesia, the legal considerations made by the judges in deciding the dispute, and the existing legal protection efforts. The findings indicate that Law No. 28 of 2014 provides automatic protection to creators for works that have been realized, encompassing both economic rights and moral rights. The judges considered the position of the Plaintiff as the legitimate heir, the substantial similarity between the two works, and the impact of the infringement on the creator's reputation.The court's decision to grant the Plaintiff's lawsuit emphasizes the importance of protecting copyright and the moral rights of creators, as well as providing a deterrent effect for violators. This study concludes that copyright protection in Indonesia needs to be enhanced through public education, improved law enforcement, and encouragement for the registration of creative works. Thus, it is hoped that a more conducive environment for the development of art and creativity, as well as respect for copyright, can be established in society.